2012
DOI: 10.1128/jvi.02253-12
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Bunyamwera Orthobunyavirus Replication by Targeted Mutagenesis of Genomic Untranslated Regions and Creation of Viable Viruses with Minimal Genome Segments

Abstract: Bunyamwera virus (BUNV) is the prototype virus for both the genus Orthobunyavirus and the family Bunyaviridae. BUNV has a tripartite, negative-sense RNA genome. The coding region of each segment is flanked by untranslated regions (UTRs) that are partially complementary. The UTRs play an important role in the virus life cycle by promoting transcription, replication, and encapsidation of the viral genome. Using reverse genetics, we generated recombinant viruses that contained deletions within the 3= and/or 5= UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Previous studies on BUNV showed that the internal parts of the UTRs are nonessential for virus viability but play an important role during virus replication (5,6). Indeed recombinant viruses carrying deletions in their UTRs are grossly attenuated in growth in cultured cells compared to wild-type (wt) BUNV, and the bigger the deletion the more attenuation the viruses display (5,6).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies on BUNV showed that the internal parts of the UTRs are nonessential for virus viability but play an important role during virus replication (5,6). Indeed recombinant viruses carrying deletions in their UTRs are grossly attenuated in growth in cultured cells compared to wild-type (wt) BUNV, and the bigger the deletion the more attenuation the viruses display (5,6).…”
mentioning
confidence: 99%
“…These minimal UTRs were defined by creating recombinant viruses that carried one deleted segment and two wt segments. However, a virus containing all minimal UTRs was not viable, but recombinant viruses carrying smaller deletions on all three segments were created; such viruses proved to be grossly attenuated (6). Serial passage of these viruses in BHK-21 cells allowed them to partially recover fitness.…”
mentioning
confidence: 99%
See 3 more Smart Citations